Strategic decision making for successful planning : solving problems for great results - Rhoads, CJ; Roth, William (Productivity Press, 2022)
Turbulence is not new to the business world. In fact, turbulence is increasing, and managers are seeing teams spinning their wheels. Management systems are in a state of crisis and operations are more complex. The old top-down operations mode no longer suffices. Today's businesses demand speed and increased accuracy, forcing everyone to re-evaluate chains of command and tear down the walls between functions. Amid the responsibilities of traditional management lies problem solving. The push is toward moving decision-making authority down the ladder to all levels. Managers are no longer equipped to or capable of making the number and variety of necessary decisions in a vacuum. The current mode is to have employees deal directly with workplace issues and take corrective action without complaint and without management involvement. Coping with this reality and preparation for these improvements in workplace problem solving requires interest and motivation. Strategic Decision Making for Successful Planning can facilitate this by demystifying and simplifying the process. The book bridges philosophy and theory and puts together a practical integration of all the tools necessary to get results from your investment of time, energy, and money. What is unique about this book is while it's based on a strong academic foundation, it does not get bogged down in the human-planning or psychological process of solving problems. It doesn't provide "pie-in-the-sky" creative solutions or a five-year process for solving problems and planning for the future. Numerous techniques and tools are included to make the book the right balance between practical and academic. The book also includes an extensive case study to illustrate points made in the text.